2008
DOI: 10.1111/j.1525-1438.2007.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA integration and messenger RNA transcription in cervical low- and high-risk squamous intraepithelial lesions in Austrian women

Abstract: The human papillomavirus (HPV) plays an important role in the progression of cervical carcinoma. High-risk (HR) HPV types have been mainly identified in cytologic high-grade squamous intraepithelial lesions (HSILs) and histologic invasive carcinoma of the cervix. We examined cervical swabs of patients with abnormal Papanicolaou (Pap) smears, diagnosed as low-grade squamous intraepithelial lesions (LSILs) including atypical squamous cells of uncertain significance or HSILs. Low-risk (LR) HPV and HR-HPV types we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
4
8
0
1
Order By: Relevance
“…For reasons of safety, these lesions are usually surgically resected. Our findings support previous suggestions that some women who undergo surgical resection may be overtreated (12,26,27,29,32).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For reasons of safety, these lesions are usually surgically resected. Our findings support previous suggestions that some women who undergo surgical resection may be overtreated (12,26,27,29,32).…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that the virus was present only at very low copy numbers and/or that only a specific region of viral DNA was integrated into the host genome. The loss of the L1 gene and its impact on viral replication after integration could lead to relatively low viral loads (7,15,24,32). Given that malignant phenotypes require continuous expression of the E6 and E7 oncogenes (13,27,39,57) and that they produce transcripts throughout the epithelium and the surface layers (12,15), it is not surprising that RNA assays detect more clinically significant infections than DNA testing, especially when samples come from the surface layers of the cervical epithelium, as in the present study.…”
Section: Discussionmentioning
confidence: 67%
“…Many previous studies have found that almost all HPV18 infections exist in an integrated form in women with invasive cancer (2,9,15,22,32). In the current study, we found a rather high proportion of ICC (57.1%) harboring only the episomal form of the virus.…”
Section: Discussionsupporting
confidence: 61%
“…We believe one explanation for this discrepancy could be the sensitivity of the method used. Methods such as Southern blotting or two-dimensional gel electrophoresis were often employed to document the physical state of the HPV genome in previous studies (2,9,10,22,27). One disadvantage of these methods is that they often require a large amount of DNA to produce a positive signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation